Application of the Convention on the Prevention and Punishment of the Crime of Genocide. (2015) - Unknown
Abstract : 1 Human rights — Genocide — Definition of genocide — Convention for the Prevention and Punishment of the Crime of Genocide, 1948 — Actus reus of genocide — Mens rea — Specific intent to destroy protected group as such — Nature of intent — Proof — Whether existence of intent can be inferred from pattern of conduct — Relationship between genocide and other violations of humanitarian law and human rights — Ethnic cleansing — Responsibility for genocide — Complicity in genocide — Duty to prevent genocide — Duty to punish genocide — Whether including duty of co-operation with International Criminal Tribunal for the former Yugoslavia — Massacre at Srebrenica International Court of Justice — Jurisdiction — Res judicata — Whether issue of jurisdiction implicitly determined at Preliminary Objections stage can be reopened at merits stage — Whether respondent State party to the Statute of the International Court of Justice at relevant time — Estoppel — Whether relevant — Provisional measures — Binding character of measures indicated before Court first stated that its measures had legal effect — Reparation for failure to comply with provisional measures — Evidence — Burden of proof — Standard of proof — Methods of proof — Relevance of findings by International Criminal Tribunal for the former Yugoslavia International criminal law — Genocide — Definition of genocide — Obligations under Genocide Convention — Role of International Criminal Tribunal for the former Yugoslavia — Proof of genocide International tribunals — International Criminal Tribunal for the former Yugoslavia — Duty of States to co-operate with Tribunal — Relationship to obligations under Article VI of the Genocide Convention — Relationship between International Court of Justice and International Criminal Tribunal for the former Yugoslavia State responsibility — Attribution — Concept of de facto organs of State — Responsibility of State for acts of persons and groups under its effective control — Nature of effective control test — Whether requiring proof of control over specific operation — Whether general control sufficient — Complicity — Genocide — International Law Commission Articles on State Responsibility, Articles 4, 8 and 16 2 State succession — Distinction between successor State and continuing State — Yugoslavia — Claim by Federal Republic of Yugoslavia to be the continuation of the Socialist Federal Republic of Yugoslavia — Separation of Montenegro from State union of Serbia and Montenegro — Whether Serbia the continuation of the State union War and armed conflict — War crimes — Crimes against humanity — Genocide — Conflict in Bosnia and Herzegovina 1992-5 — Massacre at Srebrenica